Left atrial appendage occlusion in the absence of intraprocedural product specialist monitoring: is it time to proceed alone? Results from a multicenter real-world experience - Margonato, Davide; Rizza, Vincenzo; Ingallina, Giacomo; Preda, Alberto; Ancona, Francesco; Belli, Martina; Godino, Cosmo; Agricola, Eustachio; Della Bella, Paolo; Grasso, Carmelo; Contarini, Marco; Mazzone, Patrizio (Frontiers in Cardiovascular Medicine, 2023)
Background Percutaneous left atrial appendage occlusion (LAAO) presents many technical complex features, and it is often performed under the intraprocedural surveillance of a product specialist (PS). Our aim is to assess whether LAAO is equally safe and effective when performed in high-volume centers without PS support. Methods Intraprocedural results and long-term outcome were retrospectively assessed in 247 patients who underwent LAAO without intraprocedural PS monitoring between January 2013 and January 2022 at three different hospitals. This cohort was then matched to a population who underwent LAAO with PS surveillance. The primary end point was all-cause mortality at 1 year. The secondary end point was a composite of cardiovascular mortality plus nonfatal ischemic stroke occurrence at 1 year. Results Of the 247 study patients, procedural success was achieved in 243 patients (98.4%), with only 1 (0.4%) intraprocedural death. After matching, we did not identify any significant difference between the two groups in terms of procedural time (70 ± 19 min vs. 81 ± 30 min, p = 0.106), procedural success (98.4% vs. 96.7%, p = 0.242), and procedure-related ischemic stroke (0.8% vs. 1.2%, p = 0.653). Compared to the matched cohort, a significant higher dosage of contrast was used during procedures without specialist supervision (98 ± 19 vs. 43 ± 21, p < 0.001), but this was not associated with a higher postprocedural acute kidney injury occurrence (0.8% vs. 0.4%, p = 0.56). At 1 year, the primary and the secondary endpoints occurred in 21 (9%) and 11 (4%) of our cohort, respectively. Kaplan–Meier curves showed no significant difference in both primary (p = 0.85) and secondary (p = 0.74) endpoint occurrence according to intraprocedural PS monitoring. Conclusions Our results show that LAAO, despite the absence of intraprocedural PS monitoring, remains a long-term safe and effective procedure, when performed in high-volume centers.